Training and coaching on digital marketing as an information and promotional media - Nyoman Dini Andiani; Putu Eka Kusumayani; Trianasari Trianasari; Made Windu Antara Kesiman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Panji Tourism Village that is located in Buleleng Regency, Bali has various tourism potentials such as nature, history, culture, and man-made attractions which are generally developed through training and education for micro small, and medium enterprises products as valuable and highly competitive tourist souvenirs from Panji Village. However, these various potentials have not been properly promoted in order to attract tourists. In the era of information and technology, digital marketing has become one of the keys in developing Panji Tourism Village to provide information and effective promotions to introduce cultural wisdom and natural beauty. Departing from this condition, this community service program aimed at assisting the village in increasing the promotion and branding of Panji Tourism Village through providing socialization and training related to digital marketing to POKDARWIS members in Panji Village with various social media platforms such as Instagram, Facebook, TikTok, WhatsApp, virtual tours, and websites, providing profiles, developing and managing the https://ecovilllagepanji.id website. The methods of the community service program were mainly in the form of a workshop that included lectures, discussion, and practice. The result of the community service program is the creation of creative and innovative web-based digitization of tourism village profiles. This promotional media is able to bring in tourists thereby increasing the welfare of the community.